ANALISIS KINERJA KEUANGAN DENGAN METODE ALTMAN Z – SCORE PADA PT. HERO SUPERMARKET TBK - Murwani Wulansari (Jurnal Akrab Juara, 2019)
The purpose of this study is to determine the business continuity of PT. Hero Supermarket Tbk by using secondary data in the form of financial statements from 2014 - 2018. This study uses the Altman Z Score method which is one method to assess bankruptcy of a company. The results of the study are based on data taken from PT. Hero Supermarket Tbk from 2014 - 2018 shows that the condition of the company continues to experience a decline in performance, especially in the food sales segment. The closure of several Giant outlets is the company's step in overcoming the financial condition that continues to decline. The results of the assessment by the Z Score method show that PT. Hero Supermarket Tbk experienced financial distress in 2017 (Z Score 1.66) and 2018 (Z Score 1.27). However, the business progress of PT. Hero Supermarket Tbk can still be supported by the beauty health and home furnishing segments namely Guardian and IKEA.